Evaluation of biogenic amines and nitrate in raw and pickled jurubeba (Solanum paniculatum L.) fruit - da Silva, Mônica Bartira [UNESP]; Rodrigues, Luan Fernando Ormond Sobreira [UNESP]; Monteiro, Gean Charles [UNESP]; Monar, Giovana Rafaela Stelzer [UNESP]; Gomez Gomez, Hector Alonzo; Seabra Junior, Santino; Minatel, Igor Otavio [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Springer Nature, 2019)
The presence of biogenic amines, such as histamine and tyramine, in pickled food can cause health problems, such as allergies. However, other bioactive amines may be present and can induce some diseases. Some biogenic amines can react with nitrate and form nitrosamines, compounds harmful to human health. In this research, we qualitatively and quantitatively evaluated some biogenic amines and nitrate content in jurubeba preserved in oil or vinegar. The fruits were obtained from cultivated plants, or wild plants, or they were purchased from market. Jurubeba fruit was analyzed raw and after cooking. After thermal processing, the fruits were preserved in soybean oil or vinegar and were evaluated after 1 h and at 30, 60 and 90 days of storage. Variations in the contents of biogenic amine were found depending on the place from which the fruits were obtained, as well as depending on the type of preservative and time of storage. The nitrate levels did not exceed the established limits, mainly when preserved in vinegar, which also showed the lowest levels of biogenic amines.
Keywords: Cooking; Nitrate; Polyamines; Shelf-life; Solanaceae; UPLC